PENGARUH PENAMBAHAN SERAT ALAMI ECENG GONDOK TERHADAP KUAT TEKAN BETON BERKUALITAS RENDAH - Nur Affandy; Zulkifli Lubis (U Karst, 2018)
This research will be conducted in accordance with Indonesian Standard SK SNI and foreign standard ASTM. The test object consists of a cylindrical test with the diameter of 15 cm and a height of 30 cm, and it is developed to 4 mixture variations with the amount of 2%, 4%, 6%, 8%, of total cement. The mechanical properties of concrete is being tested include concrete compressive strength. Itis tested at the age of 7 days, and then converted at 28 days, using test objects mixed with different fiber variations. The results of the test are: compressive strength test with 2% variation is 7,54MPa, compressive strength testwith 4% variation is 6,74 Mpa, compressive strength with 6% variation is 4,58 Mpa, compressive strength with 8% variation is 3.63 MPa. Maximum concrete compressive strength occurs in 2% fiber mixture, while the minimum concrete compressive strength occurs in 8%. From these results, it can be concluded that the addition of water hyacinth fiber to the mixture for low quality concrete has not been able to increase its compressive strength. Keywords:  Fiber, Water Hyacinth, Concrete Compressive Strength.  Penelitian ini akan dilakukan sesuai dengan Standar SK Indonesia SNI dan standar asing ASTM. Benda uji terdiri dari uji silindris dengan diameter 15 cm dan tinggi 30 cm, dan dikembangkan menjadi 4 variasi campuran dengan jumlah total semen 2%, 4%, 6%, 8%. Sifat mekanik beton sedang diuji termasuk kekuatan tekan beton. Itu diuji pada usia 7 hari, dan kemudian dikonversi pada 28 hari, menggunakan benda uji dicampur dengan variasi serat yang berbeda. Hasil pengujian adalah: uji kuat tekan dengan variasi 2% adalah 7,54MPa, uji kuat tekan dengan variasi 4% adalah 6,74 Mpa, kuat tekan dengan variasi 6% 4,58 Mpa, kuat tekan dengan variasi 8% adalah 3,63 MPa. Kekuatan tekan beton maksimum terjadi pada campuran serat 2%, sedangkan kekuatan tekan beton minimum terjadi pada 8%. Dari hasil ini, dapat disimpulkan bahwa penambahan serat eceng gondok ke dalam campuran beton berkualitas rendah belum mampu meningkatkan kekuatan tekannya. Kata Kunci: Serat, Eceng Gondok, Kekuatan Tekan Beton.